An effects analysis of logistics collaboration in last-mile networks for CEP delivery services. (August 2016) - Park, Hyeongjun; Park, Dongjoo; Jeong, In-Jae
Abstract: Rapid increases in courier, express, and parcel (CEP) delivery demand have made environment- and traffic-related issues important in metropolitan areas. This study analytically formulates CEP delivery behaviors in last-mile networks to estimate the effects of logistics collaboration for apartment complexes. Reflecting courier delivery behavior, the CEP delivery problem was divided into horizontal and vertical routing problems. Optimization methodologies commonly utilized in the operations research area were employed for the analytical modeling of these two routing behaviors. The proposed methodologies were applied to apartment complexes in Seoul, Korea. It was found that the financial feasibility of CEP collaboration is guaranteed when the number of households in an apartment complex exceeds about 900. From the financial perspective, CEP collaboration is applicable to 9.1–19.4% of the apartment households in Seoul. In addition, CEP collaboration was analyzed to provide a meaningful amount of social cost savings, implying its economic feasibility. The public sector's roles in stimulating CEP collaboration are discussed from financial and legislative perspectives. Highlights: CEP delivery problem was divided into horizontal and vertical routing problems. The financial feasibility of CEP collaboration is guaranteed when the number of households in an apartment complex exceeds about 900. CEP collaboration was analyzed to provide a meaningful amount of social cost savings, implying its economic feasibility.